Landscape evolution and the environmental context of human occupation of the southern pampa del tamarugal, Atacama Desert, Chile. (1st September 2020) - Workman, T. Race; Rech, Jason A.; Gayó, Eugenia M.; Santoro, Calogero M.; Ugalde, Paula C.; De Pol-Holz, Ricardo; Capriles, Jose M.; Latorre, Claudio
Abstract: As with most living organisms, human populations respond to climatic, environmental, and population pressures by transforming their range and subsistence strategies over space and time. An understanding of human ecology can be gained when the archaeological record is placed within the context of dynamic landscape changes and alterations in natural resource availability. We reconstructed the landscape evolution of the Quebrada Maní fan complex, situated along the west-facing slope of the Central Andes in the hyperarid core of the Atacama Desert, an area that contains an archaeological record that spans almost 13, 000 years. Surficial geologic mapping and dating of three 2–12 km 2 study sites, in conjunction with archaeological records and analysis of remotely sensed data for the ∼400 km 2 fan complex, was conducted to reconstruct the landscape evolution and the way of life of Paleoindian (ca. 12.8–11.5 ka) and early/late Formative (ca 2.5 to 0.7 ka) social groups. Just prior to any known human occupation, a large pluvial event in the high Andes, regionally referred to as CAPE I, impacted the Quebrada Maní fan complex from ca.18–16.5 ka. During CAPE I, the Maní fan complex was dominated by perennial stream systems that deposited well-sorted conglomerates in the upper reaches of the fan (Unit T2) and perennial wetlands (Unit B1). This pluvial period was followed by the onset of an extreme drought sometime after 15 ka, but before 13 ka, when wetlands desiccated and the distal reaches of the fan deflated. Sand sheets and sand dunes were deposited across broad reaches of the landscape and Quebrada Maní incised 3–5 m into its floodplain. This drought had profound implications for the distribution of natural resources during the subsequent pluvial event (CAPE II) that ensued from ca. 12.5–9.5 ka. Incision along the upper reaches of the fan caused a more restricted floodplain and allowed the deposition of extensive wetlands along the more distal central reaches of the fan where groundwater emerged. Paleoindian residential open-air camps were placed in these areas. Wetlands were replaced by a tree-covered floodplain during the latter portion of this pluvial event (ca. 10.5–9 ka). We found no archaeological evidence for human occupations between ∼8–2.5 ka, suggesting a lack of natural resources and/or very low hunter-gatherer population densities. During this time, Quebrada Maní incised up to 8 m into the floodplain. Mudflow deposition – typical of the present-day fan complex – initiated around 2.5 ka, likely responding to an increase in precipitation. This triggered a re-population of the fan surface by Formative agricultural groups that irrigated and extensively farmed these floodplains. By the end of the Formative, these socio-cultural groups became increasingly vulnerable to climatic changes as cut-and-fill cycles in the drainage necessitated major infrastructure adjustments, until the technologies and social-cultural convention of the epoch could not cope with environmental change and investments were abandoned by ∼0.8 ka. Highlights: Dynamic landscape evolution over the time of human habitation in the Atacama Desert. Changing resource availability linked to climate change and landscape evolution. Resource availability in the Atacama Desert during initial peopling of coastal Chile. Sensitivity of human societies to climatic and environmental change. The opening of migration corridors between the coast and Central Andes.